Research on the Hormonomics of Three Lilium Species and Their Flavonoid Diversification and Specificity - Xuanyu He; Jie Fang; Biwei Hong; Xueying Zhang; Linying Li; Yuqing He; Chaomin Chen; Shuang Liang; Zelong Xu; Chunlan Peng; Jirong Huang; Gaojie Hong; et al. (Antioxidants)
Hormonomics represents an innovative approach to plant physiology and biochemistry. We utilized hormonomics to analyze the hormone profiles of three lily bulbs. The hormones specifically enriched in BiFeng7 lily show a strong response to secondary metabolism pathways, while the Diwanghuang lily profile was predominantly focused on growth. Physiological experiments demonstrated that Diwanghuang exhibited higher levels of primary nutrients, whereas BiFeng7 displayed a greater concentration of secondary metabolites and enhanced antioxidant capacity. Through untargeted metabolomic analysis, it was revealed that BiFeng7 highly enriched four flavonoid glycosides, two flavones, one flavan, one pyranoflavonoid, two isoflavonoid O-glycosides and one rotenoid. These findings provide valuable information for developing breeding strategies and cultivation practices aimed at achieving ornamental quality, nutritional value, or stress resilience outcomes. This research demonstrates the practical application of hormone profiling in plant evaluation and offers insights into the mechanisms underlying flavonoid synthesis in lilies, serving as a reference for breeding stress-resistant lily varieties.